Potential impact of the 2024 UK Parliamentary Elections: the long shadow of Brexit - Kurecic, Petar; Kokotovic, Filip (Frontiers in Political Science, 2024)
IntroductionDespite the relative harmony of the Western states on essential security issues, the July 2024 parliamentary elections in the United Kingdom (the UK), ending with the overwhelming victory of the Labour Party, who has returned to power after 14 years, may have a significant impact on the relationship this country has with the European Union (the EU). Since Brexit, the diminished trade has contributed to a decline in the economy of the United Kingdom and it is one of the countries most significantly impacted by the “increasing cost of living” crisis.MethodsUsing an Impulse Response Function (IRF), this paper will assess the impact of a further decline of EU-UK relations as well as the policy implications of some proposals supported by significant fractions of the Conservative Party, namely tax cuts.Results and discussionThe paper concludes that a further decline in trade relations between the EU and the UK will lead to a further decline in the economy of the UK that has few feasible alternatives in terms of trading partners.